Localization and expression of C1QTNF6 in chicken follicles and its regulatory effect on follicular granulosa cells - Chong Li; Qi Li; Xing Wu; Zihao Zhang; Jing Li; Ruirui Jiang; Guoxi Li; Xiaojun Liu; Xiangtao Kang; Zhuanjian Li; Donghua Li; Yadong Tian (Poultry Science)
C1q/tumor necrosis factor-related protein 6 (C1QTNF6) is a newly discovered adiponectin analog that plays a significant role in female reproduction. However, its expression and function in chickens remain unclear. In this study, the full-length coding sequence (CDS) of chicken C1QTNF6 was cloned from adult chicken ovary. We demonstrated that the putative C1QTNF6 protein shares a highly conserved amino acid sequence with known bird homologs. Using quantitative real-time PCR (qRT-PCR) and fluorescence in situ hybridization (FISH), we observed that C1QTNF6 is widely expressed in adult chicken follicle tissues, predominantly in granulosa cells (GCs). In vitro, stimulation with follicle-stimulating hormone (FSH) and luteinizing hormone (LH) significantly increased the expression of C1QTNF6 in chicken preovulatory granulosa cells (PoGCs) and prehierarchical granulosa cells (PhGCs), respectively. Overexpression and knockdown experiments in granulosa cells revealed that C1QTNF6 affects the proliferation and apoptosis of granulosa cells, reducing the expression of steroid hormone synthesis-related genes (STAR, Cyp11a1, Cyp19a1, and 3B-HSD) and hormones (progesterone and estrogen). In granulosa cells (GCs), co-treatment with C1QTNF6 and AdipoRon (an activator of adiponectin receptors) showed that AdipoRon promotes progesterone secretion, while C1QTNF6 inhibits AdipoR1 (adiponectin receptor 1) expression. There was no synergistic effect between C1QTNF6 and AdipoRon in steroid hormone production. Collectively, these findings suggest that C1QTNF6 may be a candidate gene for regulating follicular development and reproductive performance in chickens.